2019
DOI: 10.1177/0741088319882313
|View full text |Cite
|
Sign up to set email alerts
|

Genre Knowledge and Writing Development: Results From the Writing Transfer Project

Abstract: Using a mixed-methods, multi-institutional design of general education writing courses at four institutions, this study examined genre as a key factor for understanding and promoting writing development. It thus aims to provide empirical validation of decades of theoretical work on and qualitative studies of genre and the nature of genre knowledge. While showing that both simplistic and nuanced genre knowledge promote writing development, our findings suggest that nuanced genre knowledge correlates with writin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 28 publications
4
32
0
3
Order By: Relevance
“…In doing so, students like Khadija demonstrated that their use of the Letter genre was simultaneously shaped by both their personal goals and the norms within higher education. This finding echoes previous research regarding the impact of sociocultural goals, values, beliefs, and practices on people’s genre knowledge across a variety of academic institutions and positions (Devitt, 2008; Driscoll et al, 2020; Paré, 2002; Tardy, 2003, 2016; Tardy et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In doing so, students like Khadija demonstrated that their use of the Letter genre was simultaneously shaped by both their personal goals and the norms within higher education. This finding echoes previous research regarding the impact of sociocultural goals, values, beliefs, and practices on people’s genre knowledge across a variety of academic institutions and positions (Devitt, 2008; Driscoll et al, 2020; Paré, 2002; Tardy, 2003, 2016; Tardy et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…Due to these dense social connections, such diverse students may feel the need to act as guides to higher education for their partners. Thus, in accordance with recent work by Driscoll et al (2020), diverse students and their partners may especially benefit from the social affordances of an epistolary Letter genre that allows students to address partners outside of college. These relational functions did not take place within the Best and Worst Experience genres, demonstrating the importance of allowing community college students to communicate with and offer their support to close partners via their hard-won experience in higher education.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Previous research suggests that metacognitive processing allows writers to use genre knowledge across contexts and languages and thus effectively apply their knowledge to new writing tasks or goals (e.g., Driscoll et al, 2019;Gentil, 2011;Reiff & Bawarshi, 2011;Schoonen et al, 2011). For instance, Negretti (2012Negretti ( , 2017 has examined the role of metacognition among L2 graduate student writers in facilitating effective rhetorical choices in academic genres.…”
Section: Metacognitionmentioning
confidence: 99%